Exhibiting the collections of the Spanish Crown and nobility for the nation: the Count of Valencia de Don Juan and the 1892 European historical exhibition. Issue 2 (4th May 2019) - Baillot, Élodie
ABSTRACT: This article focuses on the place and role accorded to the collections of the Spanish Crown and nobility at the Exposición Histórico-Europea organized in Madrid in 1892. It sets the exhibition in the political and cultural context of the Fourth Centenary of the Discovery of America and analyses the role of Juan Crooke y Navarrot, the Count of Valencia de Don Juan to understand how royal and aristocratic collections were instrumentalized in a bid to assert the place of the Spanish monarchy on the European and international scene and strengthen its prestige. Commissioner of Crown property, the Count of Valencia de Don Juan was one of the members of the nobility who exhibited their collections to the public. Therefore, his investment in the organization of the exhibition, as a non-professional curator, helps understand what the event meant for Spanish nobility. This enables us to gauge what role such exhibiting played in the construction of the national heritage and art historiography of Spain.